2013
DOI: 10.1111/ahg.12040
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Impact of the Lake Chad Basin Population in North Africa as Documented by Mitochondrial Diversity and Internal Variation of the L3e5 Haplogroup

Abstract: SummaryThe presence of sub‐Saharan L‐type mtDNA sequences in North Africa has traditionally been explained by the recent slave trade. However, gene flow between sub‐Saharan and northern African populations would also have been made possible earlier through the greening of the Sahara resulting from Early Holocene climatic improvement. In this article, we examine human dispersals across the Sahara through the analysis of the sub‐Saharan mtDNA haplogroup L3e5, which is not only commonly found in the Lake Chad Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…It has been well established that in the populations of eastern and central Sahel there is a discernible Eurasian genetic component introduced over a long period of time by numerous migration events from different non‐African regions (Galego Llorente et al, ; Haber et al, ; Pickrell et al, ). Successive waves of migration are clearly reflected in both maternal and paternal genetic pools (Bučková et al, ; Černý et al, ; Podgorná et al, ; Shriner & Rotimi, ) and also in autosomal datasets as shown by allele frequency based methods (Triska et al, ; Vicente et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that in the populations of eastern and central Sahel there is a discernible Eurasian genetic component introduced over a long period of time by numerous migration events from different non‐African regions (Galego Llorente et al, ; Haber et al, ; Pickrell et al, ). Successive waves of migration are clearly reflected in both maternal and paternal genetic pools (Bučková et al, ; Černý et al, ; Podgorná et al, ; Shriner & Rotimi, ) and also in autosomal datasets as shown by allele frequency based methods (Triska et al, ; Vicente et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…PCR amplification was carried out using primers and previously published protocols (Černý et al, ; Černý et al, ). These sequences have previously appeared in several publications (Černý, Čížková, Poloni, Al‐Meeri, & Mulligan, ; Černý et al, ; Černý et al, ; Černý et al, ; Čížková et al, ; Podgorná, Soares, Pereira, & Černý, ; sequences listed in Table S1) but have never been viewed together or compared with a new Y‐STR dataset. In total, we included 535 mtDNA haplotypes.…”
Section: Methodsmentioning
confidence: 99%
“…However, the significant presence of Sub‐Saharan lineages (L0, L1, L2, L3, and L4) in the two Tunisian Arab populations (35%) suggests significant admixture with indigenous Berbers, who are known to display Sub‐Saharan contributions since Paleolithic times (Frigi et al, ; Soares et al, ). This includes contributions from the Early Holocene, across the Sahel Belt, during the African Humid Period (Černý et al, ; Hernández et al, ; Podgorná et al, ; Soares et al, ), without excluding a more recent introduction in North Africa through the trans‐Saharan slave routes suggested to be mainly established in the seventh century (Harich et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies revealed the arrival of some L sublineages in North Africa across the Sahel Belt during the Early Holocene at the beginning of the African Humid Period (11 000 years ago), particularly L1b and L3e5 which are commonly found in the Lake Chad Basin (Černý, Salas, Hájek, Žaloudková, & Brdička, ; Frigi et al, ; Hernández et al, ; Podgorná, Soares, Pereira, & Černý, ; Soares et al, ). Conversely, U6 and some L sublineages were introduced from northwest Africa into Iberia probably after the Younger Dryas period (Cerezo et al, ; Hernández et al, ; Podgorná et al, ; Secher et al, ; Soares et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…64 A further study dealt with internal variation and phylogeography of another mtDNA haplogroup, L3e5, newly reported in the Lake Chad Basin. 65 Because this haplogroup is also present in north-western Africa, the existence of an ancestral population that spread across the Sahara in the early Holocene (ie, approximately 10 000-8000 years ago depending on the method used) was suggested. However, unlike L3f3, the L3e5 haplogroup is observed across linguistic boundaries in the Sahel, and its age estimate is of 10 000 years before present.…”
Section: Uniparental Mtdna and Nry Markersmentioning
confidence: 99%